LINGUOPRAGMATIC PECULIARITIES OF PRECEDENT PHENOMENON COINING AND FUNCTIONING IN ENGLISH POLITICAL DISCOURSE - Tatiana Marchenko (Гуманитарные и юридические исследования)
The article analyzes the peculiarities and stages of formation as regards a precedent phenomenon in political discourse realized in mass media. A number of communicative and cultural observations of Brexit lexeme functioning in the discourse space of English linguocultural community are specified. The author tracks the peculiarities of its actualization both in the beginning when it starts to be used as a communicatively adequate means of realizing the addressant's intention and influencing the potential addressee, and at the following stages of its associative field and pragmatic potential development. The analysis reveals that the semantic content of the precedent phenomenon under consideration includes the semes of some relevant, crucial event that directly affects all citizens in the UK and serves a stimulus for further reassessment of historical and cultural development trajectory at the national level. The associative field of the precedent phenomenon, which undergoes formation, contains such notions as an unhealthy state, an accident, inevitability, uncertainty and a crisis. The author observes the intermediary stage of precedent phenomenon formation. The process comes to an end at the final stages of the narrative, when the amount of discourse practice gradually decreases and the reflection of the categorical features typical of the precedent phenomenon takes place.